Stališča študentov do vprašanj predavateljev v predavalnici - Bratož, Silva (Sodobna pedagogika, 2020)
The relationship between the students and their lecturers plays a vital role in creating a stimulating learning environment which enables active learning and student participation in the learning process. Such an environment is often established through the use of a variety of question-asking strategies. There are, however, surprisingly few studies which focus on the use of questions at the university level. The present paper is therefore aimed at exploring the role and importance of asking questions in the higher education learning environment. We are particularly interested in the students' perception of the lecturers' questions in lectures and tutorials, the type and frequency of lecturers' questions, the students' response to the questions and the reasons for their responses. A survey which involved 252 students of different faculties and study programmes of the University of Primorska was carried out based on a questionnaire designed for the purpose of this study. The results show that the students are well aware of the importance of questions in the study process. The respondents expressed positive attitudes towards learning environments which are characterised by a question-rich communication between students and their lecturers. However, they are also critical of some lecturers' question-asking strategies, especially if they do not contribute to creating a learning environment which promotes a positive interaction between students and their lecturers and at the same time encourages student participation.
Keywords: aktivno učenje; participacija študentov; postavljanje vprašanj; študenti; učno okolje; visokošolski študij